Stent-graft placement for hepatic arterial bleeding: assessment of technical efficacy and clinical outcome in a tertiary care center. Issue 5 (May 2022) - Öcal, Osman; Mühlmann, Marc; Puhr-Westerheide, Daniel; Fabritius, Matthias; Deniz, Sinan; Wildgruber, Moritz; D'Haese, Jan; Werner, Jens; Ricke, Jens; Seidensticker, Max
Abstract: Background: To evaluate technical and clinical results of stent-graft (SG) placement for bleeding from the hepatic artery (HA). Methods: All patients intended and treated with SG deployment for bleeding from the HA at single center from January 2012 to May 2020 were retrospectively identified, and procedural details, risk factors for rebleeding, SG occlusion and mortality were analyzed. Results: Twenty-seven patients (mean age 68.8 ± 10.1) were identified, and 25 patients underwent 26 SG procedures. Twenty-four patients had recent surgery. The technical success rate was 92.8%. Three patients (3/25) had rebleeding (88% clinical success). Intensive-care need before the procedure (p = 0.013) and smaller stent-graft size (≤4 mm, p = 0.032) were related to clinical failure. Twenty-two patients had follow-up imaging. The SG maintained patency in 10 (45.4%) patients at the most recent imaging. Only placement of SG distal to the HA bifurcation (p = 0.012) was related to occlusion. The 30-day and in-hospital mortality rate after SG was 8% and 24%. In-hospital mortality was associated with the intraabdominal septic source (p = 0.010) and revision surgery (p = 0.001). Conclusion: Stent-grafts are effective in the emergent treatment of HA bleeding. Mortality is mainly related to the general condition of the patient, and stent-grafts offer time to treat underlying medical problems sufficiently. Graphical abstract: Image 1